Sky full of stars : learning to surrender to God's perfect plans - Apperson, Meg (Salem Books, 2020)
Meg Apperson grew up having a relationship with Jesus, and she always trusted God. But it wasn't until her daughter Avery--a miracle in so many ways--was born with a litany of life-threatening birth defects that she began to fully understand what it means to trust Jesus with everything.